Complement Activation Products and Cytokines in Pachychoroid Neovasculopathy and Neovascular Age-Related Macular Degeneration - Kato, Yutaka (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To investigate the characteristics of complement activation products and angiogenic cytokines in the aqueous humor in eyes with pachychoroid neovasculopathy (PNV) and neovascular age-related macular degeneration (nAMD). METHODS: This was a prospective, comparative, observational study. All patients with choroidal neovascularization were classified as PNV without polyps, PNV with polyps (polypoidal choroidal vasculopathy [PCV]), or drusen-associated nAMD according to the presence or absence of pachychoroid features and soft drusen. This study included a total of 105 eyes. Aqueous humor samples were collected from 25 eyes with PNV without polyps, 23 eyes with PCV, and 24 eyes with drusen-associated nAMD before intravitreal anti-vascular endothelial growth factor (VEGF) injection and cataract surgery in 33 control eyes. Clinical samples were measured for complement component 3a (C3a), C4a, C5a, VEGF, and macrophage chemoattractant protein 1 (MCP-1) using a bead-based immunoassay. RESULTS: C3a and MCP-1 levels were significantly higher in PCV (P = 0.032 and P = 0.039, respectively) and drusen-associated nAMD (P = 0.01 for both comparisons) than in controls, and no difference was seen in C3a and MCP-1 levels between PNV and controls (P = 0.747 and P = 0.294, respectively). VEGF levels were significantly higher in PNV (P = 0.016), PCV (P = 0.009), and drusen-associated nAMD (P = 0.043) than in controls. In PNV, the VEGF levels elevated without elevated C3a and MCP-1. CONCLUSIONS: PNV, PCV, and drusen-associated nAMD had significantly distinct profiles of complement activation products and cytokines in the aqueous humor.